Speak Up! Penguatan Kepercayaan Diri Siswa SDN Pakuajaya 02 Melalui Pelatihan Public Speaking (Altruism: The Indonesian Journal of Community Engagement, 2025)
Communication skills, particularly the ability to speak in public (public speaking), are essential competencies that need to be developed from an early age to support individuals’ future success. However, in practice, many elementary school students still face difficulties in expressing their ideas verbally due to low self-confidence, limited experience, and a lack of structured training. This community service program aims to enhance the self-confidence of students at SDN Pakuajaya 02 through public speaking training based on a participatory and experiential learning approach. The methods employed include interactive lectures, demonstrations, role plays, simulations, and direct practice in speaking in front of the class. The results indicate a significant improvement in students’ willingness to speak, their ability to express opinions, as well as their mastery of verbal and nonverbal communication aspects. In addition, the program fosters a more active and communicative learning environment. Therefore, public speaking training can serve as an effective strategy to strengthen elementary school students’ self-confidence and is recommended to be integrated into classroom learning and extracurricular activities on a sustainable basis.
Keywords: Public Speaking; Self-Confidence; Communication